Pharmaceutical applications of cyclodextrins and their derivatives - Dhiman, Priya; Bhatia, Meenakshi (Journal of inclusion phenomena and macrocyclic chemistry, 2020)
Cyclodextrins (CDs) are abundantly explored in the field of medicines for the design of various types of drug delivery systems. They are cyclic oligosaccharides carrying α (1,4) glucopyranose units and able to build aqueous soluble inclusion complexes with various small and large drug molecules. These molecules have a unique structural feature and categorized into hydrophobic, hydrophilic and ionic derivatives. Villiers and Schardinger in 1891, first described the chemical nature and types of cyclodextrin. Cramer and co-workers in 1955 illustrated their latent to make water soluble inclusion complexes with various active components. These CDs molecules are used in pharmaceutical field practically and economically to improve the stability, solubility as well as bioavailability of drug molecules. In this review article physical characteristic, chemical nature and applications of different cyclodextrin and their derivatives in different drug delivery systems and toxicological effects are engrossed.